Equitable Partnership Arrangements for MSMEs During The Pandemic - Utomo, Setiyo; Pribadi, Deny Slamet (VJJ, 2022)
MSMEs are one of the most reliable drivers of the Indonesian economy. In carrying out Cooperation, MSMEs enter into partnership agreements with prominent business actors so that there will be legal consequences for the agreement. The COVID-19 pandemic period provides separate arrangements for implementing MSMEs so that they can survive during the COVID-19 pandemic. MSMEs, in this case, can be proven from employment and as a source of state income and reduce the number of poor people. The problem in this research is how to implement partnership arrangements for MSMEs during the pandemics and how to arrange partnerships for MSMEs from a business competition perspective. This study examines and analyzes the implementation of partnership arrangements for MSMEs from the perspective of business competition. This study certainly explains the factors and impacts of the COVID-19 pandemic for MSME actors who carry out partnership agreements with prominent business actors who can provide justice.